The Multifaceted Role of Astrocyte Connexin 43 in Ischemic Stroke Through Forming Hemichannels and Gap Junctions - Liang, Zhen; Wang, Xu; Hao, Yulei; Qiu, Lin; Lou, Yingyue; Zhang, Yaoting; Ma, Di; Feng, Jiachun (Frontiers in Neurology, 2020)
Ischemic stroke is a multi-factorial cerebrovascular disease with high worldwide morbidity and mortality. In the past few years, multiple studies have revealed the underlying mechanism of ischemia/reperfusion injury, including calcium overload, amino acid toxicity, oxidative stress, and inflammation. Connexin 43 (Cx43), the predominant connexin protein in astrocytes, has been recently proven to display non-substitutable roles in the pathology of ischemic stroke development and progression through forming gap junctions and hemichannels. Under normal conditions, astrocytic Cx43 could be found in hemichannels or in the coupling with other hemichannels on astrocytes, neurons, or oligodendrocytes to form the neuro–glial syncytium, which is involved in metabolites exchange between communicated cells, thus maintaining the homeostasis of the CNS environment. In ischemic stroke, the phosphorylation of Cx43 might cause the degradation of gap junctions and the opening of hemichannels, contributing to the release of inflammatory mediators. However, the remaining gap junctions could facilitate the exchange of protective and harmful metabolites between healthy and injured cells, protecting the injured cells to some extent or damaging the healthy cells depending on the balance of the exchange of protective and harmful metabolites. In this study, we review the changes in astrocytic Cx43 expression and distribution as well as the influence of these changes on the function of astrocytes and other cells in the CNS, providing new insight into the pathology of ischemic stroke injury; we also discuss the potential of astrocytic Cx43 as a target for the treatment of ischemic stroke.